Benarkah puskesmas poned efektif? - Christina Pernatun Kismoyo; Mubasysyir Hasanbasri; Mohammad Hakimi (Jurnal Kebijakan Kesehatan Indonesia, 2012)
Basic emergency maternal care at public health center: are they effective  Background: Every pregnancy and birth is a risky event; therefore, every pregnant woman and maternity must be located as close as possible to the basic emergency obstetric care. As a health care unit, near and reachable health centers are expected to provide basic emergency neonatal and obstetric care (PONED or EmOC in primary health level). In Bantul District, there are six PONED health centers. Health centers in their implementation need an evaluation to improve or maintain a mechanism to measure whether they are good or not good. This study aimed to determine the implementation of PONED in the health centers of Bantul District.Method: This was a qualitative descriptive study. The analysis unit was service providers such as doctors, midwives, nurses, laboratory and driver as well as the head of Bantul District Health Office. The research instrument was the researcher and the tools used were cameras, tape recorders, checklists and interview guides.Results: PONED health centers were viewed more as a routine work because the service provider had not been able to understand the purpose of a good service. Emergency obstetric and neonatal care had not been fully able to be served at six health centers. Sewon I Health Center was the only PONED health center with available support system, but the availability of the service such as tools, medicine and infrastructure had not yet fully available. This was because of the rare cases of obstetric and neonatal complications handled so that the drugs and equipment available were expired and damaged. Management of emergency obstetric and neonatal referral had not been going well according to the case; thus, early referral was frequently preferable.Conclusion: The management of PONED health center’s services was more on the bureaucracy not based on the setting of emergency obstetric and neonatal care, so that the orientation of service providers was seen as a routine job. Support from the government and incentives were still very influential on service providers’ work motivation. Keywords: evaluation, PONED health center, maternal mortality rateLatar belakang: Setiap kehamilan dan persalinan merupakan kejadian berisiko, oleh karena itu setiap ibu hamil dan bersalin harus berada sedekat mungkin dengan pelayanan obstetrik emergensi dasar. Unit pelayanan kesehatan yang dekat dan mampu terjangkau oleh masyarakat puskesmas diharapkan mampu memberikan pelayanan obstetrik neonatal emergensi dasar. Di Kabupaten Bantul ada 6 puskesmas mampu PONED. Puskesmas dalam pelaksanaannya perlu adanya suatu langkah evaluasi guna meningkatkan ataupun mempertahankan suatu mekanisme yang sudah baik atau kurang baik.Tujuannya adalah untuk melihat implementasi pelayanan puskesmas mampu kegawatdaruratan Obstetrik dan Neonatal Dasar (PONED) di Kabupaten Bantul.Metode: Penelitian diskriptif kualitatif dengan unit analisis adalah petugas (dokter, bidan, perawat, laboran dan sopir) serta kepala Dinas Kesehatan Kabupaten Bantul. Instrumen penelitian adalah peneliti sendiri, alat yang digunakan kamera, tape recorder, daftar tilik, dan pedoman wawancara.Hasil: Puskesmas PONED lebih dipandang sebagai pekerjaan rutinitas karena provider pelayanan belum mampu memahami tujuan pelayanan dengan baik. Pelayanan kegawatdaruratan obstetrik dan neonatal belum seluruhnya dapat dilayani di 6 puskesmas hanya Sewon I. Sistem pendukung pelayanan PONED tersedia, namun ketersediaan pelayanan belum seluruhnya tersedia yakni; alat, obat dan infrastruktur. Hal ini karena jarangnya kasus komplikasi obstetri dan neonatus yang ditangani sehingga obat dan alat yang tersedia kadaluarsa serta rusak. Pengelolaan rujukan kasus kegawatdaruratan obstetri dan neonatal belum berjalan dengan baik sesuai dengan kasus, cenderung melakukan rujukan dini. Kesimpulan: Manajemen pelayanan puskesmas PONED lebih pada birokrasi belum berdasarkan pada setting pelayanan kegawatdaruratan obstetrik dan neonatal, sehingga orientasi petugas pelayanan dipandang sebagai pekerjaan rutinitas. Dukungan pemerintah dalam support insentif sangat berpengaruh pada motivasi kerja petugas pelayanan.